CORPORATE GOVERNANCE AND POST-MERGER PERFORMANCE: EVIDENCE FROM US BANKS - Neffati, Amira; Khiari, Wided; Lajmi, Azhaar (Copernican Journal of Finance & Accounting, 2021)
Mergers operations has currently become one of the key strategies for many firms. It becomes a tool to increase firm value when firm has reached its peak performance. This critical decision expects business performance to improve. The main purpose of this study is to analyze the impact of various governance variables, like managerial ownership, the percentage of shares held by outside directors, the board size, the audit committee size and the percentage of stock options granted to managers, on post merger banks performance and to investigate how the firm size can influence bank performance following mergers operations. It also tends to test the existence of the phenomenon of Empire building which is defined as a primary motivation for mergers operations. Empirical analysis is based on a panel data model applied to a sample of 54 banks come from the list of U.S. bank mergers over a period of 6 years from 2009 to 2015. Our results show that the increase in managerial ownership decreases the value of the deficit, therefore, improves the bank performance following mergers operations. The introduction of firm size shows that this variable is positively correlated with the value of the deficit that is used as a performance measure in this study. Our results converge with previous studies that show an improvement in the performance following bank mergers.